1996
DOI: 10.1111/j.1365-2923.1996.tb00824.x
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of knowledge levels of medical students: the Maastricht Progress Test

Abstract: The increasing international mobility of medical students has inspired the search for an international assessment format. As one step along this line, kinetics of knowledge acquisition and final cognitive levels of students were compared among one Dutch, one German and four Italian medical faculties. For this comparison, the Maastricht Progress Test (MPT) was used. For four out of the six participating faculties, it was possible to compare the level of knowledge of sixth-year students. These data showed no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
18

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 2 publications
(1 reference statement)
1
36
0
18
Order By: Relevance
“…Berkson (1993) found that "the graduate of PBL is not distinguishable from his or her traditional counterpart" (p. 85).This conclusion is consistent with a number of studies that have shown no statistically significant differences in learner performance compared to students receiving lecture-based instruction (Albano et al, 1996;Blake, Hosokawa, & Riley, 2000;Farquhar, Haf, & Kotabe, 1986;Kaufman & Mann, 1988). Culver (2000) conducted a meta-analysis of studies comparing the impact of PBL and lecture-discussion instruction and concluded that there was "no convincing evidence that PBL improves knowledge base and clinical performance" (p. 259).…”
supporting
confidence: 55%
“…Berkson (1993) found that "the graduate of PBL is not distinguishable from his or her traditional counterpart" (p. 85).This conclusion is consistent with a number of studies that have shown no statistically significant differences in learner performance compared to students receiving lecture-based instruction (Albano et al, 1996;Blake, Hosokawa, & Riley, 2000;Farquhar, Haf, & Kotabe, 1986;Kaufman & Mann, 1988). Culver (2000) conducted a meta-analysis of studies comparing the impact of PBL and lecture-discussion instruction and concluded that there was "no convincing evidence that PBL improves knowledge base and clinical performance" (p. 259).…”
supporting
confidence: 55%
“…The knowledge acquisition of international mobility medical students among Dutch, German and Italian medical schools was compared using the Mastricht Progress Testing. They concluded that this test could be used to identify corresponding cognitive levels of students on individual domains in different curricula 14,15 . A study performed with students of all six classes of two medical schools in the Netherlands, one PBL and non-PBL, showed no differences in the total test scores.…”
Section: Maria Inês Da Rosa Et Almentioning
confidence: 99%
“…Similarly, according to Johnston, Schooling and Leung (2009), problem based learning was less effective at imparting knowledge than usual teaching consisting of a lecture followed by a group tutorial. In addition, most studies have shown that there were no statistically significant differences in learner performance of problem based learning compared to students receiving lecture-based instruction (Albanese & Mitchell, 1993;Albano et al, 1996;Blake, Hosokawa & Riley, 2000;Kaufman & Mann, 1988). In a meta-analytic study comparing the impact of problem based learning and lecture-discussion instruction conducted by Culver (2000), it was concluded that there was "no convincing evidence that problem based learning improves knowledge base and clinical performance" (p. 259).…”
Section: Discussionmentioning
confidence: 99%